2021
DOI: 10.1155/2021/6670316
|View full text |Cite|
|
Sign up to set email alerts
|

Estimation Model for Bread Quality Proficiency Using Fuzzy Weighted Relevance Vector Machine Classifier

Abstract: Estimation of the quality of food products is vital in determining the properties and validity of the food concerning the baking and other manufacturing processes. This article considers the quality estimation of the wheat bread that is baked under standard conditions. The sensory data are collected in real-time, and the obtained data are analysed using the efficient data analytics to predict the quality of the product. The dataset obtained consists of 300 bread samples prepared in 15 days whose vital physical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
(24 reference statements)
0
7
0
Order By: Relevance
“…They concluded that computer vision models which are inspired by the visual cortex mechanism have great potential to be used for the quality assessment of biscuits and other baked goods. Ali et al (2021b) used a Fuzzy Weighted Relevance Vector Machine (FWRVM) classifier to estimate the quality characteristics of wheat bread baked during regular baking situations. They estimated the properties of the bread samples to formulate the features by using the sensor-based analysis employed in the industry.…”
Section: Quality Classificationmentioning
confidence: 99%
See 4 more Smart Citations
“…They concluded that computer vision models which are inspired by the visual cortex mechanism have great potential to be used for the quality assessment of biscuits and other baked goods. Ali et al (2021b) used a Fuzzy Weighted Relevance Vector Machine (FWRVM) classifier to estimate the quality characteristics of wheat bread baked during regular baking situations. They estimated the properties of the bread samples to formulate the features by using the sensor-based analysis employed in the industry.…”
Section: Quality Classificationmentioning
confidence: 99%
“…Ali et al. (2021b) used a Fuzzy Weighted Relevance Vector Machine (FWRVM) classifier to estimate the quality characteristics of wheat bread baked during regular baking situations. They estimated the properties of the bread samples to formulate the features by using the sensor‐based analysis employed in the industry.…”
Section: Applications Of Imaging Systems For the Quality Assessment O...mentioning
confidence: 99%
See 3 more Smart Citations